2017
DOI: 10.1177/1087054717744879
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Clinical Utility of ADHD Assessment Measures With Latino Families

Abstract: Objective: This study examined the incremental clinical utility of parent and teacher reports of ADHD symptomatology and functional impairment in Latino youth, as well as parent and teacher agreement with the final clinical judgment on a diagnostic structured interview. Method: Participants included 70 Latino youth (47 males, 23 females; M age = 8.13 years, SD = 2.51 years) and their parents and teachers; 60 participants were diagnosed with ADHD. Correlations, percent agreement, kappas, and regressions were ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Measure of Symptoms Over Symptom Report (Multiple Method Same Informant;n = 5) Children. Harvey et al (2009) showed that mother ratings 1 of ADHD in children 3 years of age predicted ADHD diagnosis at age 6 years beyond what is predicted using the diagnostic interview (DISK-IV; 2 Schwab-Stone et al, 1996) alone (χ2 = 11.3, p < .01; (Grace, 2017). A study by Wong (2019) investigated the incremental utility of a specific ADHD assessment (Conners-3-P; 5 Conners, 2008) in diagnosing ADHD in children and adolescents beyond a more general measure (CBCL; 6 Achenbach & Rescorla, 2001).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Measure of Symptoms Over Symptom Report (Multiple Method Same Informant;n = 5) Children. Harvey et al (2009) showed that mother ratings 1 of ADHD in children 3 years of age predicted ADHD diagnosis at age 6 years beyond what is predicted using the diagnostic interview (DISK-IV; 2 Schwab-Stone et al, 1996) alone (χ2 = 11.3, p < .01; (Grace, 2017). A study by Wong (2019) investigated the incremental utility of a specific ADHD assessment (Conners-3-P; 5 Conners, 2008) in diagnosing ADHD in children and adolescents beyond a more general measure (CBCL; 6 Achenbach & Rescorla, 2001).…”
Section: Resultsmentioning
confidence: 94%
“…Father ratings had no incremental utility over the diagnostic interview. A study on Latino youth showed that a measure of functional impairment 3 had no incremental validity over symptom report (DBD) 4 in diagnosing ADHD, χ 2 (2, 53) = 3.43, p > .05 (Grace, 2017). A study by Wong (2019) investigated the incremental utility of a specific ADHD assessment (Conners-3-P; 5 Conners, 2008) in diagnosing ADHD in children and adolescents beyond a more general measure (CBCL; 6 Achenbach & Rescorla, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations